Greenwild : the world behind the door - Thomson, Pari (Thomson, Pari. Greenwild, 2023)
Eleven-year-old Daisy Thistledown is on the run. Her mother has been keeping big, glittering secrets, and now she has vanished. Daisy knows it's up to her to find Ma-- but someone is hunting her across London. Someone determined to stop her from discovering the truth. So when Daisy flees to safety through a mysterious hidden doorway, she can barely believe her eyes--she has stepped out of the city and into another world. This is the Greenwild. Bursting with magic and full of amazing natural wonders, it seems too astonishing to be true. But not only is this land of green magic real, it holds the key to finding Daisy's mother. And someone wants to destroy it. Daisy must band together with a botanical genius, a boy who can talk with animals, and a cat with an attitude to uncover the truth about who she really is. Only then can she channel the power that will change her whole world-- and save the Greenwild itself.